2007
DOI: 10.1530/eje-07-0463
|View full text |Cite
|
Sign up to set email alerts
|

The association of interleukin-18 genotype and serum levels with metabolic risk factors for cardiovascular disease

Abstract: Objective: Circulating levels of interleukin (IL)-18 are associated with the metabolic syndrome and risk for the development of cardiovascular disease (CVD). This study investigated the association between the circulating IL-18 levels and the K137 G/C polymorphism within the IL-18 gene with metabolic risk factors for CVD in normal-weight and obese black South African women. Methods: Blood pressure (BP), body composition (dual-energy X-ray absorptiometer), visceral adiposity (computerized tomography), as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 51 publications
4
28
1
2
Order By: Relevance
“…Perhaps reminiscent of obesity-related leptin resistance, leukocytes from patients with obesity or type 2 diabetes are resistant to IL-18 (Zilverschoon et al, 2008). Polymorphisms of the IL-18 gene or its receptor have been associated with obesity (Melen et al, 2010) and metabolic syndrome disorders (Evans et al, 2007; Koch et al, 2011; Presta et al, 2009) in humans. The present and previous (Netea et al, 2006; Zorrilla et al, 2007) loss-of-function and pharmacological results support the hypothesis that endogenous IL-18 suppresses appetite and promotes energy expenditure and lipid fuel substrate utilization and may do so not only during sickness, but also in healthy adults.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps reminiscent of obesity-related leptin resistance, leukocytes from patients with obesity or type 2 diabetes are resistant to IL-18 (Zilverschoon et al, 2008). Polymorphisms of the IL-18 gene or its receptor have been associated with obesity (Melen et al, 2010) and metabolic syndrome disorders (Evans et al, 2007; Koch et al, 2011; Presta et al, 2009) in humans. The present and previous (Netea et al, 2006; Zorrilla et al, 2007) loss-of-function and pharmacological results support the hypothesis that endogenous IL-18 suppresses appetite and promotes energy expenditure and lipid fuel substrate utilization and may do so not only during sickness, but also in healthy adults.…”
Section: Discussionmentioning
confidence: 99%
“…1,4 Differences in these relationships may be explained, in part, by ethnic differences in the distribution of inflammatory gene polymorphisms and inflammatory gene expression, 5,6 insulin sensitivity, 6 obesity risk, dietary fat and specific fatty acid intake, and serum lipid concentrations between black and white SA women. 1,7 The functional -308 G4A polymorphism within the promoter region of the TNFA gene is in close proximity to the TNFA -238 G4A polymorphism (rs361525).…”
Section: Introductionmentioning
confidence: 99%
“…Further, we showed that the minor C allele was associated with elevated blood pressure in black women, independent of circulating IL-18 levels, age, and VAT [46].…”
Section: Ethnic Differences In Inflammatory Genes and Relation To Rismentioning
confidence: 68%